The ruling class : management and politics in modern Italy - Boeri, Tito.; Merlo, Antonio; Prat, Andrea (Oxford : Oxford University Press, 2010)
This volume provides an understanding of what drives the formation of a ruling class, and the relationship between politics and business firms.
Includes bibliographical references and index.
Description based on print version record.
Keywords: Business and politics -- Italy; Labor economics -- Italy; Italy -- Politics and government -- 1994-